(untitled) (Scientific journal of the Fergana State University, 2024)
The article describes the problems in the formation of military teachers of higher military educational institutions under the Ministry of Defense of the Republic of Uzbekistan as professional military pedagogues, the issues of training military pedagogues and improving their qualifications